+0

# If f(x)=x^3-8, what is f^{-1}(f(f^{-1}(19)))?

0
32
2
+272

If f(x)=x^3-8, what is f^{-1}(f(f^{-1}(19)))?

thanks

WhichWitchIsWhich  Nov 2, 2017

#2
+5242
+1

f( f-1(x)  )   =   x

Therefore

f( f-1(19) )   =   19

And

f-1(   f( f-1(19) )   )   =   f-1( 19 )

To find  f-1(19)  , lets first find  f-1(x) .

f(x)  =  x3 - 8

y  =  x3 - 8     →     y + 8  =  x3     →     (y + 8)1/3   =  x

f-1(x)  =  (x + 8)1/3      Now plug in  19  into this function.

f-1(19)  =  (19 + 8)1/3   =   271/3   =   3

hectictar  Nov 2, 2017
Sort:

#1
+443
+1

I'm assuming f^{-1} is a way of switching the input and output values, which works for this function. Therefore f^{-1}(f(f^{-1(19))) --> f^{-1} = 19, so f(x) = 19. I substituted the equation in and got x^3-8 = 19. I added 8 to each side to get x^3 = 27. To get x without an exponent, I took the cube root of each side, getting x = 3. Either way, f^{-1}(f(f^{-1(19))) = f^{-1}(19) = f(3)

helperid1839321  Nov 2, 2017
#2
+5242
+1

f( f-1(x)  )   =   x

Therefore

f( f-1(19) )   =   19

And

f-1(   f( f-1(19) )   )   =   f-1( 19 )

To find  f-1(19)  , lets first find  f-1(x) .

f(x)  =  x3 - 8

y  =  x3 - 8     →     y + 8  =  x3     →     (y + 8)1/3   =  x

f-1(x)  =  (x + 8)1/3      Now plug in  19  into this function.

f-1(19)  =  (19 + 8)1/3   =   271/3   =   3

hectictar  Nov 2, 2017

### 5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details